Resurrection of Words: A Work in Defending Formalism A Critique on Resurrection of Words A Lesson of Speeches on Literary Theory of Russian Formalists - Issa Amankhani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Contrary to the tradition of some scholars such as Forouzanfar, Homaee, Zarrinkoub who mainly discussed life and thought of the author / poet, some of the works by Dr. Shafiee Kadkani are specific and different because they have emphasized the question of form and the form of literary work apart from the content and theme, and they have sometimes written books (poetry, music) or perfectly have crafted oriented articles (based on formalist). Resurrection of Words:  A Lesson of Speeches on Literary Theory of Russian Formalists has been the most formalist work by him which is discussed in the introduction of the formalism (history, teachings and characters affected), and some of his articles have been included which have been written with inspiration from their ideas. With all the advantages that this book has (such as all works by Dr. Shafiee Kadkani), there are some criticisms leveled against it. The main criticisms are as follows: 1- incomplete expression (and possibly incorrect) background / context of the emergence of Russian Formalism, 2- lack of coherence of theories presented by the author, 3- some irrefutable and non-scientific propositions in the book and 4-, the inclusion of chapters such as "potter motif evolution in the poetry of Omar Khayyam" which is not consistent with formalism space of the book of resurrection of words.